2017
DOI: 10.1158/1078-0432.ccr-16-0806
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Circulating Tumor DNA in Pancreatic Cancer Patients Is a Prognostic Marker

Abstract: ctDNA is an independent prognostic marker in advanced pancreatic adenocarcinoma. Furthermore, it arises as an indicator of shorter disease-free survival in resected patients when detected after surgery. Clin Cancer Res; 23(1); 116-23. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
196
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(222 citation statements)
references
References 33 publications
(36 reference statements)
17
196
1
8
Order By: Relevance
“…This provides a good representation of the patient population but might have resulted in lower detection rates. In most other studies with mPDAC patients, patient flow and selection methods were unclear, hampering comparisons . Our finding that higher ctDNA detection rates occurred in patients with liver metastases of PDAC has also been reported for colorectal cancer .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This provides a good representation of the patient population but might have resulted in lower detection rates. In most other studies with mPDAC patients, patient flow and selection methods were unclear, hampering comparisons . Our finding that higher ctDNA detection rates occurred in patients with liver metastases of PDAC has also been reported for colorectal cancer .…”
Section: Discussionmentioning
confidence: 58%
“…Studies reporting exclusively on mPDAC showed detection rates of 29.3–33% . When various tumor stages were studied, a sensitivity between 38.8% and 86.1% was determined for those patients with metastatic disease . This wide range may be explained by the various methods used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has associated high MAF (>5%) with shorter OS across a variety of advanced solid tumors, including brain, lung, breast, and gastrointestinal, independent of intervening treatment . Other studies have also demonstrated the prognostic value of ctDNA MAF and that early changes in ctDNA levels can predict response to chemotherapy . Furthermore, early evidence suggests that MAF may serve as a dynamic biomarker, with early responders to durvalumab demonstrating a decrease in MAF after initiation of therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Variant calling was conducted using the LoFreqV2 (LoFreq*) mutation caller [16]. Visualizations were created in R using custom scripts (available on request) employing Bioconductor package VariantAnnotation [17] as well as the plotting framework ggplot2 [18] and further adapted in Excel. After mutations were called, percent representation was established as (number of variant reads)/(number of reference reads + number of variant reads).…”
Section: Methodsmentioning
confidence: 99%